Assessment of abuse potential of carfentanil. (6th January 2023) - Wei, Jiayun; Lai, Miaojun; Li, Feng; Chen, Yuanyuan; Li, Xiangyu; Qiu, Yi; Shen, Haowei; Xu, Peng; Di, Bin
Abstract: Carfentanil, as a fentanyl analogue, is a potent synthetic opioid. It has been controlled in many countries, and its emergence has been highlighted by many recent reports. However, although discriminative stimulus effects of carfentanil in rats had been reported, its abuse potential has not been fully evaluated. In this study, we evaluated the abuse potential of carfentanil via the tests of conditioned place preference (CPP), drug self‐administration and naloxone‐precipitated opioid withdrawal assay, compared with fentanyl and heroin. Carfentanil exhibited significant place preference at a minimum dose of 1 μg/kg in mice, whereas fentanyl and heroin induced significant place preference at the minimum doses of 100 μg/kg and 1000 μg/kg, respectively. In the drug‐substitution test in heroin self‐administered rats (50 μg/kg/infusion), carfentanil and fentanyl acquired significant self‐administrations above saline levels from 0.05–0.1 and 0.1–10.0 μg/kg/infusion, respectively. Carfentanil induced the maximum number of infusions at 0.1 μg/kg, whereas fentanyl and heroin at 1 and 25 μg/kg, respectively. In short, carfentanil showed the highest potency to induce CPP and self‐administration. Furthermore, repeated treatment with escalating doses of carfentanil, fentanyl or heroin induced typical withdrawal symptoms in mice, including a greater number of jumping and weight loss than saline group. This indicated that carfentanil could produce physical dependence similar to fentanyl and heroin. Taken together, the present study demonstrated the higher abuse potential of carfentanil compared with fentanyl and heroin. The rank order of abuse potential for these compounds is carfentanil > fentanyl > heroin. Abstract : Current research evaluated the abuse potential of carfentanil via the tests of the conditioned place preference (CPP), drug self‐administration and naloxone‐precipitated opioid withdrawal assay, compared with fentanyl and heroin. It demonstrated that carfentanil has a much higher abuse potential compared with fentanyl and heroin.